The influence of creativity, service quality, brand image, and online promotion (TikTok) on the sustainability of sales across all branches of Kiyo Café in Bandar Lampung. - Feni Lestari; Rahyono; Hiro Sejati (Yayasan Multidimensi Kreatif, 2026)
The rapid growth of the cafe industry in Bandar Lampung has created intense market competition, requiring business actors to have long-term strategies to maintain business sustainability. This study aims to analyze the influence of creativity, service quality, brand image, and TikTok online promotion on sales sustainability across all branches of Café Kiyo Bandar Lampung. Using a quantitative approach, data were collected via questionnaires from 97 respondents determined by the Lemeshow formula. The data were analyzed using multiple linear regression through SPSS 23 software. The results showed that partially, creativity, service quality, brand image, and TikTok promotion had a positive and significant effect on sales sustainability. Simultaneously, these four variables had a significant influence on sales sustainability with a coefficient of determination (Adjusted R-Square) value of 61.5%. These findings confirm that the synergy between product innovation, responsive service, a strong brand reputation, and effective social media utilization are key factors in maintaining sales stability amidst modern market dynamics.